Perspectivas de professores de ciências sobre a atuação com estudantes com deficiência intelectual na EJA - Olmos, Isabella Delamain Fernandez (2021)
Analyzing educational policies in the context of practice, it is possible to notice the secondary importance of Youth and Adult Education (EJA), which is related to Special Education from a history of denial of the educational rights, in which both were constituted through compensatory policies and welfare practices. In view of the scarcity of works that address Science Teaching at EJA in relation to students with intellectual disabilities and the importance of the teacher in relation to the ascension of these students, the research project in question has the general objective of: analyze the perspectives of Science teachers who act in Youth and Adult Education on students with intellectual disabilities, and as specific objectives: Characterize the conceptions of Science teachers about inclusion and the student with intellectual disability; (b) Characterize the pedagogical practices of Science teachers who work at EJA, specifically with students with intellectual disabilities; (c) Think about the process of including students with intellectual disabilities in EJA. The study has a qualitative approach and is characterized as a collaborative research in which, together with the researcher in the studies construction process, two science teachers working at EJA participated, one of whom had students with intellectual disabilities in their classroom. The research was carried out in a city in the interior of the state of São Paulo and the data collection procedures were divided at different times. At first, observations were made in the classroom, followed by interviews with a semi-structured script and individual reflective training meetings, built together with the participating teachers. The observations gave rise to field notes and the interviews and meetings were recorded and full transcribed. The collected data were categorized and analyzed based on the categorical content analysis. The data from the observations and interviews were used to carry out an analysis focused on the perspectives of the teachers in relation to different themes that involve the performance of the EJA Science teacher in relation to students with intellectual disabilities, and the reflective meetings were analyzed in in a way that aimed to characterize their possible reflections on the theme. The results demonstrate the different conceptions of teachers in relation to the Special Education and emphasize the training needs of specialist teachers in the face of students with intellectual disabilities and the importance of spaces that allow these teachers to reflect on their own practices, see themselves as transformers of their attitudes within the classroom and understand the countless possibilities of Science teaching as a helper for the effective teaching-learning process of students with disabilities. It is worth mentioning that the main demands brought by the participating teachers are the same and are not related to the particularities of the discipline they teach, which shows a need for training to general aspects of Special Education, despite the specific content of Science and the previous experience.